A Plea for Global Health Action Bottom-Up - Laaser, Ulrich; Dorey, Stephen; Nurse, Joanna (Frontiers in Public Health, 2016)
This opinion piece focuses on global health action by hands-on bottom-up practice: initiation of an organizational framework and securing financial efficiency are – however – essential, both clearly a domain of well-trained public health professionals. Examples of action are cited in the four main areas of global threats: planetary climate change, global divides and inequity, global insecurity and violent conflicts, and global instability and financial crises. In conclusion, a stable health systems policy framework would greatly enhance success. However, such organizational framework dries out if not linked to public debates channeling fresh thoughts and controversial proposals: the structural stabilization is essential but has to serve not to dominate bottom-up activities. In other words, a horizontal management is required, a balanced equilibrium between bottom-up initiative and top-down support. Last but not least, rewarding voluntary and charity work by public acknowledgment is essential.